My journey to Salford - Elaine Coates - Elaine Coates (BioScientist: The Salford Biomedicine Society Magazine, 2024)
Elaine is a Level 4 Human Biology and Infectious Diseases student at the University of Salford. She tells her story about her journey to Salford. She explores her life before Salford, her motivations to come back to education, and what she aims to do upon graduation from her course.